Culture, change and community justice - McNeill, Fergus (Report, 2010)
This research report reviews the international research on the management of change within community justice organisations. It specifically explores: 1. The nature and character of occupational, professional and organisational cultures in community justice. 2. How such cultures respond to, accommodate and resist change processes. 3. How and why processes of change succeed and fail in criminal justice organisations. 4. Effective approaches to the management of change in criminal justice. The review of change management is located within a wider analysis of what is known about occupational, professional and organizational cultures within criminal justice and within public sector organizations more generally, and of how practitioners respond to policy changes. This review was originally undertaken to inform the work of the Scottish Government’s Performance Improvement Strategy Group, against the backdrop of the ongoing work of the National Advisory Body. Its origins lie in the group’s recognition that both policy implementation and organisational change are complex and difficult to achieve in this area; the prospects for the success of any change initiative are likely to be determined not only by the strength of its own evidence base and theory of change, but also by the cultural and organizational conditions within which its implementation takes place. The review remains equally relevant (if not more so) in the context of the development of the Scottish Government’s Reducing Reoffending Programme.